Javenese studentsâ€™ problems in pronouncing english consonants during reading aloud activity - Nurlaili Nurlaili; Ani Susanti (Universitas Ahmad Dahlan, 2019)
This research aimed to determine Javanese students' problems in pronouncing some English consonants and to determine the possible causes of the problems. This was classified as qualitative research. The subjects of this research were thirty non-English department students in the fourth semester of Universitas AhmadÂ Dahlan who speak Javanese as their mother tongue.Â The data were collected through reading aloud task. The result of this research showed that Javanese students had Â some problem with pronouncing some English consonants. The consonants were [Î¸], [Ã°], [ê], [Ê’], [Ê¤], [Ê§], and [v].Â The problems were indicated as interlingual errors and intralingual errors. However, students had limited knowledge of place and manner of articulation of English consonants, so that most students often change and substitute the English consonants with relevant Javanese consonants.